2018
DOI: 10.1016/j.indcrop.2018.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic diversity in the Origanum genus: EST-SSR and SRAP marker analyses of the 22 species in eight sections that naturally occur in Turkey

Abstract: Origanum (L.) is a genus of herbaceous perennials with culinary and medicinal uses with many species found in the Mediterranean region. The taxonomic classification of species belonging to this genus has been studied using morphological, biochemical and genetic diversity analyses. In this study, the genetic diversity of 22 Turkish Origanum species (including 24 taxa from eight sections) was examined with 46 herbarium specimens from the Mediterranean, Eastern Anatolian, Central Anatolian, and Black Sea regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 23 publications
(64 reference statements)
2
5
0
Order By: Relevance
“…Sequence-related amplified polymorphism (SRAP) markers developed by Li and Quiros [15] have been widely applied in a number of genetic studies due to their simplicity, reliability, effectiveness and genomewide coverage [16,17]. Although the results from applications of SRAP markers in taxonomic studies could be influenced by anthropogenic or other types of selective pressure [17], during the last decade SRAP markers have been successfully applied in a number of studies on characterization of plant genetic resources and natural populations, including species from the Lamiaceae family outside the genus Lavandula [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Sequence-related amplified polymorphism (SRAP) markers developed by Li and Quiros [15] have been widely applied in a number of genetic studies due to their simplicity, reliability, effectiveness and genomewide coverage [16,17]. Although the results from applications of SRAP markers in taxonomic studies could be influenced by anthropogenic or other types of selective pressure [17], during the last decade SRAP markers have been successfully applied in a number of studies on characterization of plant genetic resources and natural populations, including species from the Lamiaceae family outside the genus Lavandula [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The genus Origanum (belonging to the Lamiaceae family) comprises 56 accepted species names recorded in The Plant List (http://www.theplantlist.org) and consists of a group of herbaceous plants characterized by edible and medicinal uses. A wide plethora of species is present in the Mediterranean region, especially Turkey, which has a rich diversity and trade, with about 15,000 tonnes of oregano exported in 2014 (Taşcıoğlu, Sadıkoğlu, Doğanlar, & Frary, ). In Turkey, the genus is represented by 22 species, among which 21 endemisms, and 32 taxa, while the ratio of endemism in the genus is 65.2% (Toncer, Karaman, Kizil, & Diraz, ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, only O. vulgare and O. onites L. have been used either as representatives of the genus Origanum in intergeneric phylogenetic investigations of the Lamiaceae family (Kaufmann & Wink 1994;Wagstaff et al 1995Wagstaff et al , 1997Bräuchler et al 2010;Bendiksby et al 2011a;Karaca et al 2013) or as outgroups in phylogenetic studies of other genera (Paton et al 2004;Walker et al 2004;Bräuchler et al 2005;Bendiksby et al 2011b). Studies focusing on the genus Origanum investigate phylogenetic relationships among the taxa of a specific morphological section of the genus (Lukas 2010;Lukas et al 2013a, b), but the majority of Origanum-based studies explore either hybridization patterns, genetic diversity or population structure, reporting among others the presence of intrageneric hybridization events (Kokkini & Vokou 1993;Gobert et al 2002;Barber et al 2007;Azizi et al 2009;Katsiotis et al 2009;van Looy et al 2009;Fatma et al 2010;Ince et al 2014;Bariotakis et al 2016;Aboukhalid et al 2017;Mechergui et al 2017;Dirmenci et al 2018a, b;Taşcioğlu et al 2018). This was also hypothesized based on morphological observations (Ietswaart 1980), highlighting the difficulty of the taxonomy within Origanum and other closely related genera in order to understand the evolutionary processes.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to a great morphological variation within and between taxa which, combined with the existence of natural hybrids (Ietswaart 1980;Kokkini & Vokou 1993;Azizi et al 2009;Lukas et al 2013b;Bariotakis et al 2016;Dirmenci et al 2018a, b), further complicates its classification. Furthermore, it has been reported that in addition to hybridization between distant taxa, the genus also shows some morphological affinities with other genera such as Thymbra, Satureja and Thymus (Ietswaart 1980;Bräuchler et al 2005Bräuchler et al , 2010Bräuchler 2018;Taşcioğlu et al 2018). Characters related to bracts, calyces and corollas are considered the most important morphological characters for the delimitation of sections and species in the genus Origanum (Fernandes & Heywood 1972;Ietswaart 1980).…”
Section: Introductionmentioning
confidence: 99%